Analisis regional keuangan inklusi perbankan syariah terhadap ketimpangan pendapatan di Indonesia - P Prastowo (Faculty of Economics, Universitas Islam Indonesia, 2018)
This research is aimed at observing the impact of financial inclusion sharia on income inequality in 33 provinces in Indonesia. This research employ FII sharia measure proposed by Sarma (2008, 2012) and panel EGLS which covers 2014 to 2016. There are four variable involved in the model, i.e. Gini index, FII, GRDP, and HDI. Based on the result, it can be shown that both FII sharia have significantly positive relationship with Gini index. This result can be interpreted that if there is an increase in FII , thus income inequality will also increase.